Breed, age, and environmental effects on bull semen in the low tropics - Sánchez Viafara, Jesús Alfonso; Vergel Martínez, Greysy Dariana; Vergel Martínez, Breysy Yuliana; Valencia Giraldo, Julián Alonso (Spei Domus, 2024)
Objective. This study aimed to identify factors that affected the semen quality of breeding bulls in the low tropics of Colombia. Materials and methods. The rest period, breed (B), and environmental (E) effects on sperm concentration and semen volume were examined in a first analysis with 399 bulls. Subsequently, breed and environmental effects on sperm concentration, semen volume, and progressive motility, in addition to breed (breed or crossbreed) effects on scrotal circumference, were examined in a second analysis performed with 1848 bulls. Results. The scrotal circumference of Jersey×Gyr bulls was significantly (p<0.05) higher than that of different breeds and F1 bulls. In addition, significant differences were also found in semen variables (p<0.01), including sperm concentration (p<0.05), which varied with the environmental conditions and was significantly higher in altitudinal zone 4 (AZ4: 150–199 meters above sea level (masl) altitude, 33.9°C environmental temperature (et), and 71.2% relative humidity (rh)) and was significantly lower in AZ5 (altitude higher than 500 masl, 23°C et, and 76% rh). In turn, the following correlations were found: the higher the semen volume, the higher progressive is the motility and sperm concentration, and the higher the sperm concentration, the higher is the progressive motility. Conclusions. AZ5 affected sperm concentration, but no significant differences were found in sperm concentration or semen volume between the breeds under study.